General Indicator of Positivity of Professional Self-Attitude and Reflexivity in the Context of the Modality of Personal Meaning of Professional Activity of Teachers - Pokrovskaya, S.E.; Giris, A.M. (Bulletin of Practical Psychology of Education, 2024)
The functional-dynamic approach to activity described by A.V. Karpov is aimed at establishing procedural means and mechanisms of dynamic organization of activity. These are the vector "motive - goal", personal meaning. From the position of the activity-meaning approach, professional activity is regulated by the subjective image of the current situation in which objects and elements have a certain value-meaning coloring, the source of which is the motive of the activity. Professional self-attitude in this article is considered as a dynamic system of semantic structures derived from the personal meaning of professional activity. Professional self-attitude over time, forming into an independent functionally autonomous motive, cannot exist in isolation (within itself), but requires a relationship with other regulatory structures. The possibilities of metacognitive and metaregulatory processes, which are steadily reflected and embodied in reflexivity, most fully correspond to this. The study is aimed at studying the relationship between professional self-attitude, reflexivity in the context of the modality of the personal meaning of teachers. Функционально-динамический подход к деятельности, описываемый А.В. Карповым, направлен на установление процессуальных средств и механизмов динамической организации деятельности. В качестве таковых выступают вектор «мотив - цель», личностный смысл. С позиции деятельностно-смыслового подхода профессиональная деятельность регулируется субъективным образом сложившейся ситуации, в котором объекты и элементы имеют определенную ценностно-смысловую окраску, источником которой выступает мотив деятельности. Профессиональное самоотношение педагогов в данной статье рассматривается как динамическая система смысловых структур - производная от личностного смысла профессиональной деятельности. Профессиональное самоотношение со временем, оформляясь в самостоятельный функционально автономный мотив, не может существовать изолированно (внутри самого себя), а требует соотношения с другими регуляторными структурами. Наиболее полно этому соответствуют возможности метакогнитивных и метарегулятивных процессов, находящих устойчивое отражение и воплощение в рефлексивности. Исследование направленно на изучение взаимосвязи профессионального самоотношения, рефлексивности в контексте модальности личностного смысла педагогов.